The Effect of the QASEE (Questioning, Answering, Sharing, Extending, and Evaluating) Learning Model on Students’ Metacognitive Skill in Nervous System Learning - Wijayani , Walia; Angraini, Erni; Saputri , Wulandari (Universitas Muhammadiyah Prof. Dr. Hamka, 2026)
Background: Metacognitive skills are important in biology learning because they help students plan, monitor, and evaluate their own thinking processes. However, these skills are often not optimally developed in conventional classrooms. Methods: This study used a quasi-experimental, nonequivalent control group pretest-posttest design to examine the effect of the QASEE learning model on students’ metacognitive skills in learning about the nervous system. The participants were Grade XI students at SMA Aisyiyah 1 Palembang, comprising 20 students in the experimental class and 16 in the control class. Data were collected using essay tests integrated with a metacognitive assessment rubric and analyzed using paired and independent t-tests. Results: Both classes improved, but the experimental class taught using the QASEE model achieved higher posttest metacognitive scores than the control class. The paired t-test showed significant improvement in both groups (p < 0.05), and the independent t-test showed a significant difference between the posttest scores of the experimental and control classes (p < 0.05). Conclusions: The QASEE learning model outperformed conventional learning in supporting students’ metacognitive skills for learning about the nervous system. This model has the potential to serve as an alternative biology learning strategy that encourages more active and reflective thinking.